Injury to the Vertebral Endplate-Disk Complex Associated with Osteoporotic Vertebral Compression Fractures - Ortiz, A.O.; Bordia, R. (American Journal of Neuroradiology, 2011)
BACKGROUND AND PURPOSE: MR imaging has been used extensively for identification and determination of chronicity of VCF. A major emphasis is placed on identification of edema or fluid clefts within the vertebral body. Little attention is given to other spinal structures such as vertebral endplate, intervertebral disk, posterior elements, and facet joints, spinal ligaments, and paraspinal musculature. Our objective was to assess the incidence of vertebral endplate and adjacent-level intervertebral disk injury as seen on MR imaging studies of patients with acute or subacute painful osteoporotic vertebral compression fractures. MATERIALS AND METHODS: We performed a retrospective review of spine MR imaging examinations in all patients who presented to our institution for subsequent treatment with vertebral augmentation. One hundred six patients had MR imaging studies and reports available for review. A total of 211 acute or subacute vertebral compression fractures were identified in this group of patients. All fracture levels were evaluated for the presence or absence of vertebral endplate and/or associated intervertebral disk injury. RESULTS: Detailed analysis of the images showed a high incidence of endplate and intervertebral disk injury. Superior vertebral endplate injury (39%) was more common than inferior endplate injury (12%), while the combination of both was observed in 29% of the levels. The pattern of intervertebral disk injury was similar, with injury to the disk above the fracture (36%) more common than injury to the disk below the fracture level (15%). While the official radiology reports correctly identified the vertebral compression fractures, they did not mention or describe the associated vertebral endplate or disk abnormalities. CONCLUSIONS: Vertebral endplate injury is commonly seen in osteoporotic vertebral compression fractures. Furthermore, this is frequently associated with injury to the adjacent intervertebral disk. These findings are often under-reported but should be described because they may have important implications for symptomatic presentation, patient management, and outcomes. OVCFosteoporotic vertebral compression fracture